Application of Appropriate Technology (TTG) for Processing Inorganic Waste at the Tasikmalaya Waste Bank (BST) in Singaparna District, Tasikmalaya Regency - Sugandi, Wahyu K; Suryadi, Edy; Dwiratna, Sophia (Edumedia Solution, 2025)
The potential of plastic waste in Singaparna District, Tasikmalaya Regency, based on field observations, can reach up to 10 tons per month, with its utilization not yet optimal. The plastic waste collected at the Tasikmalaya Waste Bank (BST) typically consists of intact plastic bottles and cups. In addition to being used for handicrafts, the BST group sells it directly to plastic recycling factories at a price of IDR 8,000 per kg. According to their calculations, this price does not cover the operational costs of BST. Meanwhile, the price of plastic that has been shredded into granules can reach up to IDR 14,000 per kg. The Agricultural Tools and Machines Laboratory of the Department of Agricultural Engineering and Industrial Management at Padjadjaran University has developed a plastic shredding machine capable of reducing plastic to the smallest size with a sieve diameter of 14 mm, with a machine capacity of 30 kg/hour, which is expected to assist in addressing issues faced by the partners. The goal of this PKM (Community Service Program) activity is to assist the BST Tasikmalaya group in utilizing plastic waste, either as raw material for handicrafts or to be sold directly in the form of plastic granules. The implementation method for this activity includes the application of appropriate technology, specifically a plastic shredding machine in Singaparna District, Tasikmalaya Regency, which covers the production of the shredding machine, the application of the machine, socialization through lectures on utilizing plastic as a recyclable product to address waste problems, guidance and training on operating the plastic shredding machine, and maintenance procedures for the machine.